2004
DOI: 10.1038/ncb1146
|View full text |Cite
|
Sign up to set email alerts
|

Centriolar SAS-5 is required for centrosome duplication in C. elegans

Abstract: Centrosomes, the major microtubule-organizing centres (MTOCs) of animal cells, are comprised of a pair of centrioles surrounded by pericentriolar material (PCM). Early in the cell cycle, there is a single centrosome, which duplicates during S-phase to direct bipolar spindle assembly during mitosis. Although crucial for proper cell division, the mechanisms that govern centrosome duplication are not fully understood. Here, we identify the Caenorhabditis elegans gene sas-5 as essential for daughter-centriole form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
176
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 30 publications
5
176
1
1
Order By: Relevance
“…The prominent spindle pole localization of WDR62 is shared by another MCPH protein, abnormal spindle microcephaly related gene (ASPM) (Higgins et al, 2010;Pulvers et al, 2010). In contrast, other MCPH proteins, microcephalin, cdk5rap2, CENPJ, CEP152, and STIL are principally centrosomal in their localization (Delattre et al, 2004;Fong et al, 2008;Varmark et al, 2007;Zhong et al, 2006). Interestingly, ASPM and WDR62 are most frequently mutated in MCPH accounting for 50% and 10% of cases, respectively (Thornton and Woods, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent spindle pole localization of WDR62 is shared by another MCPH protein, abnormal spindle microcephaly related gene (ASPM) (Higgins et al, 2010;Pulvers et al, 2010). In contrast, other MCPH proteins, microcephalin, cdk5rap2, CENPJ, CEP152, and STIL are principally centrosomal in their localization (Delattre et al, 2004;Fong et al, 2008;Varmark et al, 2007;Zhong et al, 2006). Interestingly, ASPM and WDR62 are most frequently mutated in MCPH accounting for 50% and 10% of cases, respectively (Thornton and Woods, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of PCM proteins cdk5rap2 or pericentrin, with the latter also genetically linked to primordial dwarfism with associated microcephaly, similarly altered neuroprogenitor division in embryonic mouse brains with reduced cell proliferation and enhanced cell cycle exit (Buchman et al, 2010;Lizarraga et al 2010). However, unlike MCPH proteins (cdk5rap2, CENPJ, STIL, Cep152, Cep135 and Cep63) with well characterized functions in centriole duplication (Barrera et al 2010;Delattre et al, 2004;Hatch et al, 2010;Hussain et al, 2012;Sir et al, 2011;Vulprecht et al, 2012), we have demonstrated that WDR62 is not principally a centrosome protein and its depletion did not obviously impact on centrosome number or structure during interphase. We cannot completely exclude WDR62 functions as an integral centrosomal protein.…”
Section: Discussionmentioning
confidence: 99%
“…The coiled-coil protein SPD-2 (spindle defective 2) was required to recruit the ZYG-1 protein kinase that, in turn, recruits the spindle assembly abnormal proteins SAS-6 and SAS-5 as a prerequisite for procentriole assembly and, finally, SAS-4, required for the addition of centriolar microtubules ( Kirkham et al 2003;Leidel and Gonczy 2003;Dammermann et al 2004;Delattre et al 2004Delattre et al , 2006Kemp et al 2004;Pelletier et al 2004Pelletier et al , 2006Leidel et al 2005). The functional homologs of these five proteins are highly conserved (Fig.…”
Section: The Core Pathway Of Centriole Assemblymentioning
confidence: 99%
“…9,13 Recent work in C. elegans has shown that ZYG-1 kinase, a likely functional homologue of SAK/PLK4, recruits a complex of two coiled-coil molecules, SAS-6 and SAS-5, that are necessary for the formation and elongation of a central centriole precursor tube. 7,[14][15][16][17][18] The assembly of the singlet microtubules (MTs) onto the central tube is dependent on SAS-4, another coiledcoil centriolar protein. 7 The high degree of conservation of these molecules is permitting examination of the mechanisms of centriole biogenesis in a number of other organisms.…”
mentioning
confidence: 99%